α-Mangostin hydrogel film with chitosan alginate base for recurrent aphthous stomatitis (RAS) treatment: study protocol for double-blind randomized controlled trial - Vitamia, Cszahreyloren; Iftinan, Ghina Nadhifah; Latarissa, Irma Rahayu; Wilar, Gofarana; Cahyanto, Arief; Mohammed, Ahmed Fouad Abdelwahab; El-Rayyes, Ali; Wathoni, Nasrul (Frontiers in Pharmacology, 2024)
Background: Recurrent Aphthous Stomatitis (RAS) is a common ulcerative disease of the oral mucosa which is characterized by pain, and recurrent lesions in the oral cavity. This condition is quite painful, causing difficulty in eating, speaking and swallowing. Topical medications have been used for this condition, but the obstacle in using topical medications is the difficulty of achieving drug effects due to saliva wash out. This problem can be overcome by film hydrogel formulation which can protect the ulcer and reduce the pain to some extent. α-mangostin is a xanthone isolated from the rind of the mangosteen fruit. One of the activities of α-mangostin is anti-inflammatory effects, which operate through the characteristic mechanism of inhibiting the inflammatory response. This protocol study aims to investigate the efficacy of an α-mangostin hydrogel film with a chitosan alginate base for recurrent aphthous stomatitis (RAS) in comparison with a placebo over a period of 7 days. Study design: This is a two-arm, double blinding, randomized controlled trial enrolling patients with RAS. The efficacy test of α-mangostin Hydrogel Film will be tested against the placebo. Patients with RAS will be allocated randomly into the two arms and the hydrogel film will be administered for 7 days. The diameter of ulcer and visual analog scale (VAS) score will be used as the primary efficacy endpoint. The outcome measure will be compared between the two arms at the baseline, day 3, day 5, and at the end of 7 days. Discussion: The purpose of this clinical research is to provide scientific evidence on the efficacy of α-mangostin hydrogel film with a chitosan alginate basis in treating recurrent aphthous stomatitis. The trial is expected to improve our capacity to scientifically confirm the anti-inflammatory effectiveness of α-mangostin compounds in a final formulation that is ready to use. Trial registration: NCT06039774 (14 September 2023).